2016
DOI: 10.1038/ncomms13403
|View full text |Cite
|
Sign up to set email alerts
|

High-performance shape-engineerable thermoelectric painting

Abstract: Output power of thermoelectric generators depends on device engineering minimizing heat loss as well as inherent material properties. However, the device engineering has been largely neglected due to the limited flat or angular shape of devices. Considering that the surface of most heat sources where these planar devices are attached is curved, a considerable amount of heat loss is inevitable. To address this issue, here, we present the shape-engineerable thermoelectric painting, geometrically compatible to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(76 citation statements)
references
References 57 publications
(88 reference statements)
4
71
0
1
Order By: Relevance
“…Heat transfers faster to the conformal film increasing its temperature higher than the taped sample, which is attributed to empty spaces between the film and substrate. It is worth noting that this protocol to obtain conformal films does not require the use of elevated temperatures, as is the case for the recently reported inorganic conformal inks 43…”
Section: Resultsmentioning
confidence: 97%
“…Heat transfers faster to the conformal film increasing its temperature higher than the taped sample, which is attributed to empty spaces between the film and substrate. It is worth noting that this protocol to obtain conformal films does not require the use of elevated temperatures, as is the case for the recently reported inorganic conformal inks 43…”
Section: Resultsmentioning
confidence: 97%
“…One advantage of the radial structure is the good fit to the curved surfaces of many heat sources compared to traditional flat‐plate TEGs. For such a curved heat source, methods to mitigate geometric mismatch must be devised . If the heat source consists of a hot fluid running through a circular pipe, which is true for many cases, a radial TEG can be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Rogers et al has reported that the compliant and stretchable TE materials in the form of coils that can be integrated into the compliant three-dimensional forms (Nan et al, 2018). Some other works have also demonstrated that by the technique of thermoelectric painting, people can achieve the shape-engineering of high-performance TE materials (Sun et al, 2014;Park et al, 2016).…”
Section: Introductionmentioning
confidence: 99%